2007
DOI: 10.1038/nm1676
|View full text |Cite|
|
Sign up to set email alerts
|

T cell–encoded CD80 and 4-1BBL induce auto- and transcostimulation, resulting in potent tumor rejection

Abstract: To reject tumors, T cells must overcome poor tumor immunogenicity and an adverse tumor microenvironment. Providing agonistic costimulatory signals to tumor-infiltrating T cells to augment T cell function remains a challenge for the implementation of safe and effective immunotherapy. We hypothesized that T cells overexpressing selected costimulatory ligands could serve as cellular vehicles mediating powerful, yet constrained, anatomically targeted costimulation. Here, we show that primary human T cells expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
215
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(224 citation statements)
references
References 50 publications
7
215
0
2
Order By: Relevance
“…Importantly, recent experimental studies performed in mice have demonstrated that the stimulation of IS formation results in a potent tumor rejection involving GzmB polarization. 44 The demonstration here that CD8 ϩ T cells establish GzmB-mediated IS with tumorigenic cells in human GBM points the way toward strategies for tumor immunotherapy and identifies potential molecular targets, [45][46][47] which will permit the stimulation of CTL synapse formation.…”
Section: Org) Both Cd8mentioning
confidence: 89%
“…Importantly, recent experimental studies performed in mice have demonstrated that the stimulation of IS formation results in a potent tumor rejection involving GzmB polarization. 44 The demonstration here that CD8 ϩ T cells establish GzmB-mediated IS with tumorigenic cells in human GBM points the way toward strategies for tumor immunotherapy and identifies potential molecular targets, [45][46][47] which will permit the stimulation of CTL synapse formation.…”
Section: Org) Both Cd8mentioning
confidence: 89%
“…Even if T cells are generated with high avidity for antigens, the success of adoptive T-cell immunotherapy cannot be guaranteed because of uncertainty of its persistency and reactivity in vivo. 4 The genetic modification of T-cell function allowed naı¨ve T cells transformed into tumor-reactive effector cells harboring high affinity T-cell receptors (TCRs) as well as chemokine and cytokine receptors that enhance their survival and homing properties. 5 Rosenberg and co-workers 6 reported from the first clinical trial that 2 out of 16 patients, who received autonomous lymphocytes expressing MART-1 TCR, underwent regression of liver and lung helium metastases and showed complete regression over 2 years later.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to improvements in CAR design, other approaches have been investigated to improve CAR-modified T cell function and persistence. While costimulation has most often been incorporated within the CAR construct, T cell function can be augmented by provision of costimulation in formats that do not include the costimulatory domain within the CAR [42]. Engineering T cells to express both the CAR and costimulatory molecule ligands such as CD80 or CD86 may ensure delivery of a costimulatory signal to adoptively transferred T cells in the absence of tumor-derived costimulation [42].…”
Section: Design Of Chimeric Antigen Receptorsmentioning
confidence: 99%
“…While costimulation has most often been incorporated within the CAR construct, T cell function can be augmented by provision of costimulation in formats that do not include the costimulatory domain within the CAR [42]. Engineering T cells to express both the CAR and costimulatory molecule ligands such as CD80 or CD86 may ensure delivery of a costimulatory signal to adoptively transferred T cells in the absence of tumor-derived costimulation [42]. Another approach involves modifying T cells to express both a firstgeneration CAR and a separate chimeric receptor that contains a distinct extracellular antigen-binding domain and a costimulatory domain, but no CD3f signaling domain (Fig.…”
Section: Design Of Chimeric Antigen Receptorsmentioning
confidence: 99%